Estimates of the Replacement Costs of Commercial and Backyard Avocado Trees in South Florida - Edward A. Evans; Jonathan H. Crane (EDIS, 2009)
FE825, a 4-page article by Edward A. Evans and Jonathan H. Crane, estimates how much it would cost to replace all commercial and residential backyard avocado trees in Miami-Dade, Broward, Palm Beach, and Lee Counties, in light of the recent discovery of the redbay-laurel wilt disease complex, which can destroy both commercial and backyard avocado trees. Includes references. Published by the UF Department of Food and Resource Economics, December 2009.